THE CONTRIBUTIONS OF WHATSAPP GROUP AS ENGLISH WRITING LEARNING MEDIUM FOR HIGH SCHOOL STUDENTS DURING THE COVID-19 PANDEMIC - Ficha Fahala; Ahmad Talib; Muh. Tahir (Universitas Negeri Makassar, 2022)
This research aims to determine the contributions of WhatsApp group as an English writing learning medium for high school students. This research applied a study case method through a qualitative approach. To achieve the research objectives, the data were collected through interviews. The participants in this research were eight eleventh grade students of SMA Negeri 1 Luwu Timur, who had met the criteria determined by the researchers (purposive sampling). The results show the contributions of WhatsApp group as a medium in learning writing, such as: (1) students found WhatsApp Group as a fun and simple learning medium (2) WhatsApp group keeps students active during the learning process (3) WhatsApp group can build good communication between students and teacher (4) WhatsApp group make it easier for students to get the learning material (5) WhatsApp group help students to study writing via online (6) WhatsApp group can be used as a media to promote individual learning.